Altered Resting-State EEG Microstate in Idiopathic Sudden Sensorineural Hearing Loss Patients With Tinnitus - Cai, Yuexin; Chen, Suijun; Chen, Yanhong; Li, Jiahong; Wang, Chang-Dong; Zhao, Fei; Dang, Cai-Ping; Liang, Jianheng; He, Nannan; Liang, Maojin; Zheng, Yiqing (Frontiers in Neuroscience, 2019)
In order to clarify the central reorganization in acute period of hearing loss, this study explored the aberrant dynamics of electroencephalogram (EEG) microstates and the correlations with the features of sudden sensorineural hearing loss (SSNHL) and tinnitus. We used high-density EEG with 128 channels to investigate alterations in microstate parameters between 25 SSNHL patients with tinnitus and 27 healthy subjects. This study also explored the associations between microstate characteristics and tinnitus features. There was a reduced presence of microstate A in amplitude, coverage, lifespan, frequency and an increased presence of microstate B in frequency in SSNHL patients with tinnitus. According to the syntax analysis, a reduced transition from microstate C to microstate A and an increased transition from microstate C to microstate B were found in SSNHL subjects. In addition, the significant negative correlations were found between Tinnitus Handicap Inventory (THI) scores and frequency of class A as well as between THI scores and the probability of transition from microstate D to microstate A. While THI was positively correlated with the transition probability from microstate D to microstate B. To sum up, the significant differences in the characteristics of resting-state EEG microstates were found between SSNHL subjects with tinnitus and healthy controls. This study suggests that the alterations of central neural networks occur in acute stage of hearing loss and tinnitus. And EEG microstate may be considered as a useful tool to study the whole brain network in SSNHL patients.